Multifocal extranodal non-Hodgkin lymphoma: A clinicopathologic study of 37 cases in Greece, a Hellenic Cooperative Oncology Group Study - Economopoulos, T.; Papageorgiou, S.; Rontogianni, D.; Kaloutsi, V.; Fountzilas, G.; Tsatalas, C.; N. Pavlidis; Pectasides, D.; Papageorgiou, E.; Dimopoulos, M. (Oncologist, 2005)
The purpose of this retrospective study was to illustrate the clinicopathological features of patients presenting with multifocal extranodal non-Hodgkin lymphoma (NHL). Among 810 patients with NHL, 37 cases (4.2%) were found to have multiple extranodal involvement (two or more sites). There were 24 men and 13 women, with a median age of 63 years. The majority of these cases (n = 26) had gastric or intestinal (GI) involvement with or without other extranodal sites. Lung along with another extranodal site was relatively common in the present series. Stratification of the 37 cases according to the International Prognostic Index (IPI) showed that 89% of the patients belonged to the high-risk groups. Diffuse large-B -cell lymphoma (DLBCL) accounted for 62%, and mucosa-associated lymphoma tissue (MALT) lymphoma accounted for 27% of all cases. After induction treatment with anthracycline-based regimens, complete remission was achieved in 21 patients (57%), partial remission was achieved in six patients (16%), and seven patients (19%) had no response, while three patients (8%) were nonevaluable. In conclusion, multifocal extranodal NHL is a heterogeneous group of diseases. The majority of them arise at various sites in the GI tract. DLBCL was the most frequent histological subtype followed by MALT lymphoma. Risk group, as defined by the IPI, was predictive of survival. ©AlphaMed Press.
Keywords: Extranodal; Lymphoma; Multifocal